FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX SEBELUM PANDEMI - R. Nia Marotina; Karima Tamara (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
This research aims to see the effect of financial performance using return on assets and return on equity as a measuring tool, good corporate governance using the size of the board of directors and the number of audit committees as a measuring tool, on the value of the company using price to book value (PBV). ) as a measuring tool. This research is a descriptive comparative study with a quantitative approach. Sources of data in this study come from secondary data using documentation methods through websites and research journals. This study uses purposive sampling technique, namely with certain criteria. The results of this sampling are 13 companies listed on the Jakarta Islamic Index for the 2016-2019 period. This study uses multiple linear regression analysis. The results of this study indicate that partially return on assets only has a significant effect on firm value, while simultaneously return on assets, return on equity, board size and number of audit committees have a significant effect on firm value. Keywords: Financial Performance, Good Corporate Governance, and Company Value.